(untitled) (Research, Society and Development, 2025)
Ovariohysterectomy (OH) in companion animals is generally considered safe, with few adverse effects compared to the benefits to public health and animal welfare. However, it can be associated with a variety of complications, some of which may arise years after the procedure. Therefore, this case report aims to describe the late complications of ovariohysterectomy performed in a nine-year-old poodle dog, in which nylon clamps were used for hemostasis of the ovarian pedicles and uterine stump. Clinical examination and complementary tests revealed a fistula in the right paralumbar fossa and foreign bodies in the caudal pole of the kidneys. Therefore, an exploratory celiotomy was performed, in which adhesiolysis, dissection of the granulomas, removal of the nylon clamps, total splenectomy and transection of the remaining ovary were performed. Additionally, debridement of the fistulated site was performed. These findings highlight the importance of the correct choice of hemostatic materials and the surgeon’s experience for the correct performance of HO, with nylon clamps being a predisposing factor for late complications. The surgeon’s competence, combined with careful selection of materials and continuous assessment of the patient, plays a fundamental role in achieving positive results and reducing post-HO complications.